Thermophysical Properties Enhancement in Construction Materials Based on Cement and Plaster - Amine, Lachheb; Rachid, Saadani; Miloud, Rahmoune (International Journal of Sustainable Construction Engineering and Technology, 2022)
Enhancing insulating power of buildings envelope saves energy costs and minimizes associated CO2 emissions. The development of materials with good thermal performance is a major challenge. This work shows the effect of incorporating different additions on the thermal properties of composites based on plaster and cement through a series of experiments. The additives used are among the most widespread wastes in Morocco. Dozens of new samples based on cement and plaster have been prepared and experimentally characterized by the box method to develop environmentally friendly materials with the best thermal characteristics. The results show that increasing incorporation rate of additives significantly improves thermophysical properties of based materials. The addition of 4% alfa and 6% of coffee grounds in plaster matrix and the replacement of cement by 50% of ashes in mortar and concrete record the low thermal properties including thermal conductivity, diffusivity, effusivity and specific heat. The good performance of new materials encourages us to integrate them into the building envelope. The results of the annual simulations carried out for a typical building located in Meknes indicated that the use of these proposed materials has significant economic and environmental benefits. A reduction of 50% in energy and a limitation of 3029.13 kgCO2eq/yr are observed thanks to an effective combination between the developed materials